2007
DOI: 10.1016/j.nuclphysb.2007.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Eikonal approximation in AdS/CFT: Conformal partial waves and finite N four-point functions

Abstract: Abstract:We introduce the impact parameter representation for conformal field theory correlators of the form A ∼ O 1 O 2 O 1 O 2 . This representation is appropriate in the eikonal kinematical regime, and approximates the conformal partial wave decomposition in the limit of large spin and dimension of the exchanged primary. Using recent results on the two-point function O 1 O 1 shock in the presence of a shock wave in Anti-de Sitter, and its relation to the discontinuity of the four-point amplitude A across a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
379
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 156 publications
(401 citation statements)
references
References 14 publications
(40 reference statements)
22
379
0
Order By: Relevance
“…Our findings are consistent with AdS/CFT predictions [27][28][29] where it was found that for n 1, γ(n, ) ∝ −n 4 / 2 while for n 1, γ(n, ) ∝ −n 3 / for graviton exchange dominance in the five dimensional bulk.…”
Section: Jhep11(2015)083supporting
confidence: 92%
See 3 more Smart Citations
“…Our findings are consistent with AdS/CFT predictions [27][28][29] where it was found that for n 1, γ(n, ) ∝ −n 4 / 2 while for n 1, γ(n, ) ∝ −n 3 / for graviton exchange dominance in the five dimensional bulk.…”
Section: Jhep11(2015)083supporting
confidence: 92%
“…of (2.7) is dominated by the exchange of a twist-2 and spin-2 operator exchange. In the language of AdS/CFT, the particle is a graviton that dominates the scattering amplitude in the Eikonal limit [27][28][29]. As in the previous case the anomalous dimension goes as ∼ 1/ 2 for large spin in the r.h.s.…”
Section: Casementioning
confidence: 75%
See 2 more Smart Citations
“…This uses the conformal impact parameter representation introduced in [39] and extensively discussed in [17]. We then compute the hadronic Compton tensor, which is the basic object that allows one to compute the γ * p → γp cross section.…”
Section: Hadronic Compton Tensor In the Regge Limitmentioning
confidence: 99%